1993
DOI: 10.1007/bf00805801
|View full text |Cite
|
Sign up to set email alerts
|

Zinc can influence ornithine decarboxylase activity in rat thymus cells

Abstract: The thymus of young rats contained a high basal activity of ornithine decarboxylase (ODC). Treatment with zinc sulphate caused a slight increase of thymic ODC activity within 6 hours and a more marked enhancement (three-fold) in the spleen 24 h after treatment. In spite of the high activity of thymic ODCin vivo, ODC was not detectable in primary cultures of rat thymocytes, but was early and largely induced after treatment with Concanavalin A (Con A). The presence of 0.1 mM zinc in the medium increased the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ornithine decarboxylase (ODC), the key enzyme in polyamine biosynthesis, is essential for cell proliferation and can be induced following growth stimuli [9,10]. It has been shown that ODC activity can be enhanced by Zn2+ supplementation in certain rat tissues or in cultured thymocytes [11,12]. In the present study we have investigated the effect of restricted Zn2+ availability on ODC induction and expression in L1210-DFMOr cells [13], an ODC-overproducing cell line which has been selected for resistance to the inhibitor difluoromethylornithine (DFMO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ornithine decarboxylase (ODC), the key enzyme in polyamine biosynthesis, is essential for cell proliferation and can be induced following growth stimuli [9,10]. It has been shown that ODC activity can be enhanced by Zn2+ supplementation in certain rat tissues or in cultured thymocytes [11,12]. In the present study we have investigated the effect of restricted Zn2+ availability on ODC induction and expression in L1210-DFMOr cells [13], an ODC-overproducing cell line which has been selected for resistance to the inhibitor difluoromethylornithine (DFMO).…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type L1210 cells were utilized under the same experimental conditions. Thymocytes were isolated from rat thymus glands as previously described [12], diluted in RPMI 1640 medium as described above, but at a density of 107/ml and treated with 10 ,ug/ml concanavalin A for 4 h. DTPA (0.6 mM) and ZnSO4 (0.4 mM) were added 15 min before the mitogen. At the time indicated after treatment, cells were harvested and washed with PBS.…”
mentioning
confidence: 99%